Analisis dan Evaluasi Struktur dan Skala Upah Melalui Metode Point Method pada UKM Batik XYZ - Muhammad Hasbi Ashidiqii; Sylvia Putri Tjahyadi; Muhammad Fauzzan Farid; Tassyah Rizam Eka Putri; Indra Refipal Sembiring (Jurnal Pijar, 2026)
This study evaluates the compensation system and proposes a wage structure and scale for a batik SME in Bogor City. Using the Point System method and a quantitative descriptive approach involving 22 employees, the study found that all employees earned below the 2026 Bogor City Minimum Wage (IDR 5,161,769), while average salaries covered only 53% of Decent Living Needs (KHL). A negative mid-to-mid value (-2.55%) also indicated wage compression. The proposed structure consists of four job grades with more proportional salary ranges and is projected to increase the salary budget by 20.6% to improve internal equity and compliance with labor regulations.